Assessing the association between musculoskeletal injury and mental health in rugby players—A cross-sectional study - Mordicai Atinga; Jasmit Shah; Sarah Karanja; Mark Lutomia Lumbasi; Miriam Wambui Ndungu; Sarah Kiburi; James Ondiege; Njalalle Baraza (PLoS ONE, 2026)
Background Musculoskeletal injuries are common among athletes and can negatively affect both physical and psychological wellbeing. Beyond physical disability, injuries have been linked to poor mental health, loss of athletic identity, and increased substance use. In low- and middle-income countries (LMICs), where awareness and management of mental health remain limited, the psychological burden of sports injuries may be underrecognized. Rugby, a physically demanding contact sport, has one of the highest rates of injury, but little is known about how such injuries influence mental health and related outcomes in African contexts. This study explored the relationship between musculoskeletal injuries and health outcomes—including mental health, physical functioning, identity, and substance use—among rugby players in Kenya. Methodology We conducted a cross-sectional survey between October 2024 and November 2024 among rugby players from ten clubs across Kenya. Eligible participants were adults aged 18 years and above, recruited using convenience sampling. Data were collected through electronic questionnaires that captured demographics and included various psychological and health assessment tools. Summary statistics were presented as medians and interquartile ranges for continuous data and frequencies and percentages for categorical data. The non-parametric Kruskal–Wallis test was used to compare the continuous variables and Fisher’s exact test was used to compare the categorical variables between group associations. Results A total of 400 players were recruited and included in the analysis. The median age was 24.0 years (IQR 21.0–27.0) and majority were males (89.8%). Over half (52.5%) reported a significant injury in the past two years, most commonly affecting the knee (41.0%), ankle (32.4%), and shoulder (21.0%). The mean GHQ-12 score was 22.4 (SD = 5.6), indicating some burden of mental health symptoms, and injured players had significantly higher GHQ-12 scores (p = 0.001). On the SF-12, the mean physical and mental component scores were 84.5 (SD = 12.6) and 60.5 (Sd = 8.6), with injured players reporting lower physical scores (p < 0.001). The AIMS shower strong athletic identity overall with injured players demonstrating significantly higher social identity scores (p = 0.007). The ASSIST revealed that 72.8% had ever used substances, with alcohol (71.8%), cannabis (19.5%), and tobacco (13.3%) being the most common; cannabis use was significantly higher among injured players (p = 0.002). Conclusion Musculoskeletal injuries among rugby players were associated with poorer mental health, reduced physical functioning, and greater cannabis use. These findings underscore the need for integrated injury management approaches that address both physical rehabilitation and psychological wellbeing, including mental health screening, counselling, and substance use surveillance.